Personal Branding, Party Image, and Political Promotion as Determinants of Voter Decision-Making: The Mediating Effect of Voting Interest in Indonesia’s Local Elections - Intan Agustiani; Dikdik Harjadi; Dede Djuniardi (UIN Sunan Gunung Djati, 2025)
In 2024, Indonesia will hold general elections to choose legislative candidates at the central and regional levels. Kuningan Regency in West Java also held legislative candidate elections at the regency level. There's an interesting phenomenon where legislative council members consistently win seats in the two previous election cycles. In the context of political marketing, the candidate is the object that must be valuable to be chosen, making competition with a marketing approach interesting to study. To analyze this phenomenon, this research was conducted to determine the factors influencing voters' decisions in choosing legislative candidates for the Kuningan District DPRD. The focus of this research is the analysis of personal branding, party image, and promotions conducted by candidates, with voting interest as a mediating variable. Personal branding is the uniqueness built from a person's skills, experience, and personality, which can shape positive perceptions and a tendency to choose. Party image is related to the impression formed in the public's mind regarding political parties. Promotion is an effort made to introduce candidates to political marketing strategies thru media or public publication channels that are responsive to voters. The object of study is a legislative member from the PDIP party who has consistently won a legislative seat in the Kuningan District Council for two period. The respondents in this study were 200 people who are loyal voters for the candidate and are members and supporters of the PDIP party. The research method uses quantitative analysis with data collected using questionnaires and analyzed using SEM PLS. The research results show that all hypotheses are supported, all independent variables have a positive and significant effect on the decision to choose a candidate, and there is an Voting Interest that mediates the relationship between personal selling, party image, and promotion on the decision to choose. These results indicate that candidates who are consistent in their personal branding have a higher chance of being re-elected, supported by the party's image and promotions that generate strong voting interest and influence legislative candidate voting decisions. Practically, this research has implications for candidates, political parties, and policymakers. Candidates need to manage their personal branding not just for image, but to cultivate genuine interest in the eyes of voters. Political parties need to maintain a consistent image thru reputation, integrity, and tangible performance in order to generate public interest. Meanwhile, policymakers can leverage these insights to design political education strategies and campaign regulations that not only raise awareness but also encourage active voter interest in the democratic process.